Das große Verbesserungspotenzial in der multimodalen Basisbehandlung der peripheren arteriellen Verschlusskrankheit (pAVK): ein Aufruf zum flächendeckenden Ausbau der pAVK-Gehtrainingsgruppen in Deutschland - Dovzhanskiy, Dmitriy; Behrendt, Christian Alexander; Görtz, Hartmut; Uhl, Christian; Classen, Simon; Marchiori, Elena; Neufang, Achim; Rümenapf, Gerhard; Stavroulakis, Konstantinos; Rother, Ulrich; Jaron, Vera; Kunert, Katrin (Gefässchirurgie, 2023)
Walking exercise is one of the most important pillars of the treatment of peripheral arterial disease (PAD). Walking exercise in groups under supervision is especially effective. In Germany, a nationwide offer of walking exercise groups is not available. Thus, the German Society for Vascular Surgery and Vascular Medicine (DGG e. V.), represented by the Committee “PAD and the diabetic foot”, launched a nationwide campaign to promote the establishment of local walking exercise groups. This article appeals to vascular physicians to establish and shape local walking exercise groups. Ways of creating such groups are described.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Basic therapy; Claudicatio intermittens; Peripheral arterial disease; Rehabilitation sports; Vascular Surgery and Vascular Medicine; Walking exercise